ROLE OF MATRA BASTI IN SECONDARY AMENORHOEA WITH INTERNAL MEDICINE - Borakhade.Vasundhara Ramdas (International Journal of Applied Ayurved Research, 2015)
Absence of menstruation for three to six months after menarche without pregnancy is secondary amenorhoea. Most common causes are hormonal imbalance and stress. In this case a 24 year female comes to OPD with absence of menses since 4-5 months ,she is having same problem from last 3 years taking Regular hormonal treatment. Now the condition is that without taking Tb. primolute N there is no menstruation .Due to fear of side effect she approach us for ayurvedic treatment .After taking proper history I started treatment from the next day with Matrabasti with abhyantara kalpa like Chandra prabhavati, yograj guggul and sutshekhar ras On the fifth day of basti treatment she is having start with menstruation .This procedure was followed for next three cycles. Every month patient came ten days before the menstruation and given the same treatment. Now she is having regular menses without taking hormonal therapy. From this it is proven that Matrabasti is useful in secondary amenorhoea due to hormonal imbalance.